Problematic Analysis of the National Free School Lunch Policy on Vocational Education - Eliza, Fivia; Jamaris, Jamaris; Marsidin, Sufyarma; Sardi, Juli; Habibullah, Habibullah; Fadli, Radinal (invotek, 2024)
Free school lunch policies have been shown to improve student health and well-being in many countries. However, the implementation of these policies in low- and middle-income countries faces significant challenges, including logistical issues, budget constraints, and coordination among stakeholders. This study aims to analyze the challenges faced by countries that have already implemented free lunch programs, with a focus on the lessons learned by Indonesia in preparing a similar policy. This research is a literature review, utilizing a Systematic Literature Review (SLR) method in accordance with the PRISMA guidelines. The study focuses on the 10 highest-cited articles from the Scopus database published between 2019 and 2024 that discuss the implementation of free lunch programs in various countries. Document analysis was employed to extract and synthesize key challenges and solutions. Findings show that the main challenges include difficulties with food distribution in remote areas, lack of sustainable budgets, and suboptimal coordination between the government and schools. The implications of the study highlight the importance of strengthening logistics infrastructure and improving coordination across sectors in Indonesia to ensure smooth implementation of the school lunch policy. Future research needs to focus on the long-term impact of the lunch program on academic achievement and innovative logistics models that can be adapted for remote areas in Indonesia.